Initial and boundary value problems for partial functional differential equations. (1997) - Ntouyas, S. K.; Tsamatos, P. Ch.
Abstract : In this paper we study the existence of solutions to initial and boundary value problems of partial functional differential equations via a fixed-point analysis approach. Using the topological transversality theorem we derive conditions under which an initial or a boundary value problem has a solution.